The Risk Factors of Phlebitis in The Installation of Intravent Catalysts - Hajar Acintya Farah; Bambang Sarwono; Heru Supriyatno (Poltekkes Kemenkes Semarang, 2021)
Background: A hospital is a health service facility that allows nosocomial infections, namely phlebitis. Phlebitis is a complication of intravenous catheter placement that is characterized by redness, pain, swelling, and fever. The high rate of phlebitis in various countries is due to the risk factors that predispose to the incidence of phlebitis due to intravenous catheter placement.Objective: This study aims to determine the risk factors for phlebitis in intravenous catheter placement.Methodology: This study uses an observational analytic method with a cohort design. The study was conducted on 27 February - 14 March 2020 with 22 samples taken using purposive accidental sampling in the inward and RST surgery Dr. Soedjono Magelang. The instrument used was an observation sheet designed by researchers that had been tested by experts and a standard operational checklist for infusion. Data analysis uses a chi-square test and multiple logistic regression.Results: The incidence of phlebitis was 7 respondents (31.8%) and the associated risk factors were the type of infusion fluid (RR = 4.37 CI 95% 1.09-17.58; p-value 0.020). While the factors of age, sex, nutritional status, chronic diseases, types of injection drugs, insertion location, duration of installation, nurse skills, installation techniques, and catheter size were not related to the incidence of phlebitis (p-value 0.05).Conclusion: Although several factors are not related to the incidence of phlebitis, these factors can be a support for the incidence of phlebitis.